The Development of the Geography of Tourism in Poland in the 20th Century - Dziegieć, Elżbieta; Liszewski, Stanisław (Turyzm/Tourism, 2002)
The aim of this review is to present the development of the Polish geography of tourism, particularly its main research areas and greatest academic achievements of the last 70 years. In order to delimit the development stages, official dates have been presumed dividing the period into four sections: before World War II, 1945-1970, 1970-1990 and after 1990. The authors have taken into account the significant political, economic and social changes which have affected tourism in Poland, as well as its academic research. They also referred to books and academic journals about tourism, as well as all the habilitation theses on the geography of tourism that have appeared.